Examining local community understanding of mangrove carbon mitigation: A case study from Ca Mau province, Mekong River Delta, Vietnam. (February 2023) - Nguyen, Hai; Harper, Richard.J.; Dell, Bernard
Abstract: Payments for carbon services (C-PFES) is a mechanism used to meet national emission reduction targets via either forest protection or reforestation. However, while carbon is a unique environmental service traded in national and international markets, there are challenges in implementing C-PFES schemes at the local level. Simply put, the views of local participants who will undertake the abatement activities have not been considered. By analysing at the local level the views of potential sellers, potential buyers and intermediaries, this paper investigated the feasibility of applying C-PFES for mangroves in Ca Mau province, Vietnam. While local stakeholders had a strong understanding of the likely impacts of climate change on their production and were aware of the environmental roles of mangroves, the carbon sequestration capacity of mangroves was rarely mentioned, and this will be a challenge in implementing a C-PFES scheme. While potential sellers and intermediaries showed strong support for C-PFES, potential buyers were less likely to join the scheme. As the carbon sequestration capacity of mangroves can also be purchased by international entities, it is recommended that the scope of the current Vietnamese C-PFES scheme be broadened to allow participation of entities from outside Ca Mau province, including private companies, government agencies and international investors. We also identified the need for education training programs to enhance stakeholders' perspectives prior to the implementation of C-PFES at the local level. This study provides insights for countries with mangrove ecosystems seeking to implement a C-PFES.